REPRESENTATION OF THE ANGER OF THE PROPHET MUSA IN THE QUR'AN FROM THE PERSPECTIVE OF THE PSYCHOLOGY OF HUMAN INTRAPERSONAL COMMUNICATION IN ISLAM - Sikumbang, Ahmad Tamrin; Munardi, Benny; Zaein, Achyar; Kholil, Syukur (Psikis : Jurnal Psikologi Islami, 2022)
This study aimed to analyze the anger of the Prophet Musa in the Qur'an from the perspective of the psychology of human intrapersonal communication in Islam. This research used qualitative methodology in the language paradigm, which aimed to find the essence of the meaning of words and sentences in a text. The subject of the study was the Qur'an verses related to the Prophet Musa's anger. Data collection techniques were library research and documentation. Data analysis techniques included collecting, reducing, presenting, and drawing credible conclusions. The results of the study stated that human psychology in a positive self-concept would have a self-confidence effect and have the strength and power to vent anger on people who make mistakes. In the psychological approach of human intrapersonal communication, Prophet Musa’s anger went through a long process of sensation, perception, memory, and thinking which determined the attitude of anger, which had a positive effect.